Adjusting The Factors Affecting The Internal Rate of Return on Investment in Production-Sharing Oil Contracts to Stabilize The Interests of The Investor - Ghavidast, Neda; Khakzar Bafruei, Morteza (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
The financial system of production-sharing contracts has more complications in comparison with other oil contracts, especially production participation contracts. The financial system and the conditions governing the payment and repayment of production-sharing contracts can be modeled at various times during the implementation of these contracts, and by using this modeling, the profitability of the plan for the parties of the contract can be evaluated, and an optimal decision can be made based on the results of the modeling In the research literature, the economic analysis of oil production-sharing contracts in the middle stages of contract implementation has not been done or very little has been done from the perspective of the investor. In this paper, economic mathematical modeling of oil production-sharing contracts with the aim of maximizing the investor’s internal rate of return is presented. In this model, the data is derived from a real contract that has been delayed for approximately 30 months, as well as payment and repayment forecasts for the next 56 months. To optimize the model, we have simulated monthly payments and repayments were generated by observing their minimum and maximum values in 2000 times and each time, the rate of return was calculated, and the optimal payment and repayment amount was determined. Results specify that if the contract has been delayed, the investor can improve the internal rate of return by managing the timing of payments.